Modelo didáctico para la enseñanza de la gramática en preuniversitario - Martínez Méndez, Mario Alejandro; Ferrer Gardona, Juan; Méndez Díaz, Beatriz (My University, 2020)
El presente artículo parte de la problemática relacionada con la enseñanza descriptiva de la gramática. Tiene como objetivo proponer un modelo didáctico que contribuya al perfeccionamiento de la enseñanza de la gramática en preuniversitario en función de la comprensión, el análisis, y la construcción textual. Para el desarrollo de la investigación se utilizaron mé todos teóricos y empíricos. Se brindan las dimensiones de qué y cómo enseñar gramática. Se asume para ello la teoría de la lingüística del discurso, la nueva gramática de la Real Academia Española, y el enfoque cognitivo, comunicativo y sociocultural.

This article starts from the problem related to the descriptive teaching of grammar. It aims to propose a didactic model that contributes to the improvement of grammar teaching in pre-university based on comprehension, analysis, and textual construction. Theoretical and empirical methods were used for the development of the research. The dimensions of what and how to teach grammar are provided. The theory of speech linguistics, the new grammar of the Spanish Royal Academy, and the cognitive, communicative and sociocultural approach are assumed for this.
Didactic model for teaching grammar in pre-university
Keywords: Modelo Didáctico; Didáctica de la Gramática; Enseñanza Preuniversitaria; Funcionalidad Textual; Didactic Model; Grammar Didactics; Pre-university Education; Textual Functionality; Didáctica; Lingüística